(untitled) (KYAMC Journal, 2019)
Adult intussusception is a rare disease, found 5% of all cases of intussusceptions and almost 1%-5% of bowel obstruction. In adults, intussusception is typically due to a pathologic lead point within the bowel, which is malignant in over 50% of cases. Inflammatory fibroid polyp (also known as Vanek’ stumour) is an uncommon, non-neoplastic proliferating lesion which can develop in various parts of the gastro-intestinal tract but most commonly in the gastric antrum and the ileum. Here we present a case of 35 years old lady with symptoms intermittent lower abdominal pain. USG of abdomen revealed as right adnexal complex cyst with thicken gut wall. She was underwent laparotomy and found ileo-ileal intussusception but no adnexal pathology. Segmental resection done where histopathology reported as loops of intussusception containing inflammatory fibroid polyp. KYAMC Journal Vol. 9, No.-4, January 2019, Page 190-193